The Impact of total public expenditure in education on economic growth in Kenya - Mutia, Sharon Kavuo (Strathmore University, 2018)
This paper examines the effect of additional public expenditure in education on economic growth in Kenya. At the onset it was hypothesized that additional education expenditure would lead to economic growth since the latter hypothesis is backed by the theory of human capital. This study utilizes the Vector Error Correction Model (VECM) to determine if additional public expenditure in education causes GDP growth in the Kenyan context. The study finds that there exists a long run relationship between education expenditure and economic growth. Further, it is found that education expenditure is a significant determinant of GDP growth after controlling for certain factors. Based on these findings, it may be of use to research further on the type of education expenditure that yields the best results be that recurrent or capital expenditure. Additionally further research could delve on the impact of public expenditure in education at the different levels of education (primary, secondary and tertiary)
A Research project Submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Science in Financial Economics at Strathmore University
Keywords: public expenditure; Economy; Gross Domestic Product; education